Compatibility of Cloxacillin Sodium with Selected Intravenous Drugs during Simulated Y-Site Administration. Issue 3 (March 2015) - Sullivan, Thomas; Forest, Jean-Marc; Leclair, Grégoire
Background: Data regarding Y-site compatibility of intravenous (IV) cloxacillin sodium with other drugs are scarce and incomplete. Objective: To establish the compatibility of IV cloxacillin with 89 injectable drugs during simulated Y-site administration. Methods: Cloxacillin sodium (10 mL, 100 mg/mL) was combined with 89 undiluted IV drugs (10 mL, each). Tests were duplicated and performed at room temperature. Visual evaluation and a light obscuration particle count test were performed on 1 of the 2 solutions immediately after mixing. The second mixture underwent visual evaluation after 15 minutes, 1 hour, and 4 hours, followed by a particle count test at 4 hours. Drugs were considered incompatible if the mixture precipitated or became turbid within the 4-hour period or exceeded the particle count limit allowed by Test 1.B of USP <788> initially or at 4 hours. Results: Of the 89 tested drugs, 64 were compatible for up to 4 hours. The remaining 25 drugs were incompatible. Of these incompatible drugs, 16 were identified visually, and 9 were identified by the light obscuration particle count test. Conclusions: Sixty-four IV drugs were found to be compatible with cloxacillin via simulated Y-site, whereas 25 drugs were found to be incompatible with the antibiotic. The light obscuration particle count test should be used to complement visual evaluation when samples do not precipitate immediately.